High-speed electro-thermal modelling of a three-phase insulated gate bipolar transistor inverter power module - Zhongfu Zhou (International Journal of Electronics, 2010)
In this article, a high-speed electro-thermal (ET) modelling strategy to predict the junction temperature of insulated gate bipolar transistor (IGBT) devices of a three-phase inverter power module is presented. The temperature-dependent power loss characteristics of IGBT and diode devices are measured and stored in lookup tables, which replace the conventional complicated physics-based compact models. An inverter is modelled as a voltage controlled voltage source, which allows the inverter-based power train simulation to be carried out in the continuous time domain with a large simulation time-step (1 ms). Using the simulated sinusoidal voltage and current components of the inverter output, the given pulse width modulation mode, the conduction time (duty ratio) and the current of the devices are extracted. Based on the lookup tables, on-times and conduction currents of devices, the average power loss over each simulation time-step is calculated, which is then fed into the inverter thermal model to predict the devices' temperatures. The advantage of the proposed model is that an accurate ET simulation of inverter for long real-time (many minutes) operation can be carried out within an acceptable computational time using a standard modern personal computer. Both simulation and experimental validation have been carried out, and an excellent agreement has been achieved between the simulation and experimental data.